Effect of Physical Exercise on Autonomic Nerve Function in Irritable Bowel Syndrome - Tenzina, Karma; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2015)
Background: Irritable bowel syndrome (IBS) may be associated with autonomic nerve dysfunction. However, moderate to vigorous physical exercise cause improvement of this nerve function. Objective: To observe the effect of moderate physical exercise on the autonomic nerve activity by analysis of HRV in patients with Irritable bowel syndrome. Methods: This prospective study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in 2013. For this purpose, 77 male patients aged 20-50 years with IBS were included in the study. They were subdivided into IBS-D (24 patients), IBS-C (26 patients) and IBS-A (27 patients) and were selected from the OPD, Gastroenterology, BSMMU. 28 apparently healthy male were studied as control. HRV parameters were recorded prior to onset of physical exercise and after completion of 3 months of brisk walking. For assessing autonomic nerve function, some time domain measures of HRV were recorded by Polyrite D. ANOVA, Independent sample t-test and paired t-tests were used for statistical analysis. Results: The pre-exercise values of mean R-R interval, Max/Min ratio, SDNN,RMSSD, NN50%, PNN50% were significantly(p<0.05) lower and mean heart rate was significantly (p<0.05) higher in all IBS patients compared to control. The post exercise data showed mean HR was significantly decreased in IBS-A and SDNN & RMSSD were significantly increased in IBS-C and IBS-A. Conclusion: This study concluded that parasympathetic activity decreased in patients with IBS, which was improved after regular moderate physical exercise of 3 months. DOI: http://dx.doi.org/10.3329/jbsp.v9i1.22790 Bangladesh Soc Physiol. 2014, June; 9(1): 17-21